The Impact of Reward System on Employee Performance: : An Analytical Study of Private Universities in Erbil City / KRG, Iraq - Shirin Jamal Mohammad Rashid (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
This study investigates the correlation between the rewards system and employees’ performance in private universities in Erbil city. Furthermore, it also aimed to investigate the impact of rewards (intrinsic and extrinsic) on employee performance at private universities in Erbil city. For that, the researcher applied simple random sampling to collect data from 221 employes from private universities in Erbil city. The researcher used statistical tools like correlation and regression to analyze the data. To find out the result, the researcher used the statistical software SPSS 21. The findings of the study suggest that intrinsic and extrinsic rewards impact the ability of employees in private universities in the Erbil Kurdistan region to perform better. The results also show that specific recognition and a conducive work environment impact employees' performance in Erbil city's private universities. The current study is limited to the Kurdistan region of Erbil city only. However, Future research can focus on a broader sample size. Future studies can analyze the impact of reward systems in other research contexts or industries, not academics. Future research can also broaden the sample size for more generalizability of the findings. Future research may also focus on adding more versatile variables for analyzing rewards impact on the performance of employees.